Sense and purpose of a privilege regarding canon 360 - Sánchez-Girón Renedo, José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The manifestation of conscience to the Superior, as regards the religious, implies to let their Superior know certain aspects of their person and of their live which are considered to belong to their own intimacy. Canon Law forbids the religious Superiors to induce in any way their subjects to give them a manifestation of conscience. Much more so, it is understood, to oblige them to do it. The religious can give it voluntarily to his Superior who, unless the subject agrees to, cannot reveal to anybody what he has come to know through these means; neither to take it into account in his government. On the contrary, in the Society of Jesus this practice is compulsory. The Superior is also bound to keep secret unless the Jesuit frees him from it. Nevertheless, he can always make use of the acquired knowledge in the government. So me characteristics of the Society's charisma and way of governing may explain this peculiarity.
Keywords: manifestation of conscience; discernment; spiritual government; secret